Theoretical study on the mechanism and kinetics of ring-opening polymerization of cyclic esters initiated by tin(II) n-butoxide - Chanchai Sattayanon (2018)
The coordination-insertion mechanisms of ring-opening polymerizations (ROP) of γ-valerolactone (GVL), δ-valerolactone (DVL) and l-lactide (LL) initiated by tin(II) n-butoxide were investigated using hybrid density functional theory at the B3LYP level with a mixed basis set. Analysis of geometries and corresponding energies revealed six intermediate states (including two transition states) observed in all three ROP reactions, which confirmed a coordination-insertion mechanism. Calculated energy profiles demonstrated exothermicity for each ROP reaction with a rate-determining step found for the first transition state that involved the attraction of an oxygen atom of the monomer to the metal atom of the initiator. By using the resulting energy barriers and transition state theory, the thermal rate constants could be obtained with the predicted rates of GVL and LL found to be equal and faster than that of DVL. In addition, by comparisons of the ring-strain energies and the barrier heights, we found that the effect of ring strain was at most only a partial driving force for the ROP reactions. © 2014 Elsevier B.V.